Permainan Ludo untuk Meningkatkan Keterampilan Kolaborasi Siswa dalam Pembelajaran Matematika - Ulhusna, Mishbah; Putri, Sri Diana; Zakirman, Zakirman (Universitas Pendidikan Ganesha, 2020)
Mathematic is one of the difficult and scary subjects. Sometimes, the students feel afraid and it makes them feel forced and uncomfortable. Indirectly this situation would affect the students’ learning outcomes and another reason was the lack of activities in learning mathematics which could train and enhance students’ collaborative skill. Learning would be more meaningful if it involved peers to build students’ knowledge. Therefore, the purpose of this research was to find out the effect of Ludo game in improving students’ collaborative skill. This research was quasi-experimental with the sample of 21 students on third grade in SD 19 Nan Sabaris. The instrument used students’ collaborative assessment sheet. The data analyzed by using effectiveness test with paired sample t-test. The conclusion showed that there were significant different on students’ collaborative skill between the students who were taught by using Ludo and the students who were taught by using conventional learning.